Meta-Synthesis: Improving Mathematical Problem-Solving Skills Through Problem-Based Learning Models - Irma Nilta Muna; Masrukan Masrukan; Scolastika Mariani; Isnaeni Rosyida (EduMa: Mathematics education learning and teaching, 2025)
Mathematical problem-solving skills are an essential component of mathematics education and support the achievement of Sustainable Development Goal (SDG) 4 on Quality Education. Indonesian students still demonstrate relatively low performance in mathematics. According to the 2022 Programme for International Student Assessment (PISA), Indonesia achieved an average mathematics score of 379, ranking 68th out of 76 countries. This result highlights a substantial gap between expected global mathematical competencies and actual student performance. Innovative learning approaches are required to improve students’ abilities not only in obtaining correct answers but also in understanding, analyzing, and solving problems independently. One promising approach is Problem-Based Learning, which emphasizes contextual problems and student-centered learning. This study employed a Systematic Literature Review using the PRISMA framework to ensure a transparent and systematic literature selection process. A total of 210 articles were identified from Google Scholar, ScienceDirect, and DOAJ databases. After applying inclusion and exclusion criteria, 10 articles published between 2020 and 2025 were selected and analyzed using thematic synthesis techniques. The analysis focused on improving mathematical problem-solving skills and evaluating the effectiveness of the PBL model. The findings revealed that the implementation of PBL had a positive and significant impact on students’ mathematical problem-solving skills across elementary, junior high, and senior high school levels. In addition, PBL enhanced students’ conceptual understanding and collaboration skills, making it an effective strategy for mathematics learning.